Clinical signs, imaging findings, and outcome in twelve cats with internal ophthalmoparesis/ophthalmoplegia. (28th December 2017) - Hamzianpour, Negar; Lam, Richard; Tetas, Roser; Beltran, Elsa
Abstract: Objective: To retrospectively evaluate the clinical signs, imaging findings, and outcome of feline internal ophthalmoparesis/ophthalmoplegia. Procedure: Medical records were reviewed from 2008 to 2015. Inclusion criteria included cats that presented with internal ophthalmoparesis/ophthalmoplegia, underwent diagnostic imaging, and had follow‐up information available. Results: Twelve cases of feline internal ophthalmoparesis/ophthalmoplegia were identified. Nine cats were unilaterally affected, and three cats were bilaterally affected. Affected cats had a median age of 10.54 years (range 5.75 to 13.17), and both sexes of varying breeds were affected (nine males; three females). Clinical signs including abnormal mental status ( n  =   9; 75%) and additional neurologic abnormalities ( n  = 10; 83%) were observed. Magnetic resonance imaging and/or computed tomography (MRI/CT) of the head were performed in ten cats, revealing a mass lesion in all cases with varying locations. Multicentric lymphoma was diagnosed in two cats via abdominal ultrasound and cytology. All twelve cats were euthanized due to deterioration of clinical signs and/or quality‐of‐life concerns. Median time from diagnosis to euthanasia was 3.5 days (range 0 to 80 days). Conclusions: Feline internal ophthalmoparesis/ophthalmoplegia rarely presents as the sole clinical sign in a referral hospital. Advanced imaging (MRI/CT) may be necessary to reach a definitive diagnosis in these cases. However, abdominal ultrasound would be advocated in cats with systemic clinical signs as a less expensive and less invasive diagnostic test to further investigate the possible etiology of internal ophthalmoparesis/ophthalmoplegia prior to advanced imaging. Feline cases with internal ophthalmoparesis/ophthalmoplegia associated with other intracranial signs and/or systemic clinical signs have a poor prognosis.